The blood supply of the islets of Langerhans in the Mongolian gerbil. - Chilvers, E R (1983)
Ink injection studies and point counting have been used to follow and quantify the development of vascularity in the islets of Langerhans of the Mongolian gerbil. Vascularization is essentially a postnatal event in this species. Initially, islet capillaries form part of the general capillary bed of the gland, but subsequently they develop a direct arteriolar supply and venous drainage. The capillary connections with the exocrine bed are retained to form the basis of an insulo-acinar portal system. The volume fraction of islet vascularity remains constant at 19% from birth to adulthood, while the volume fraction of the intra-insular capillaries increases gradually in the first week; it accounts for half the total islet vascularity by day 14 and two thirds of total islet vascularity in the adult.